A Study of Time and Sex Distribution of Road Traffic Accident Cases in Western Uttar Pradesh - Preeti Verma; Subhash C Gupta; Menaal Kaushal; Gagan Singh (Medsci Publications, 2015)
Introduction: Globalization has improved the socio-economic sta- tus resulting in more use of vehicles and this resulted in increased number of road traffic accident (RTA) cases. Objectives of the study were to study the gender difference in RTA cases and also to study the time distribution i.e. difference in occurrence of RTAs as per time of the day, day of the week and the various months of the year Methods: A hospital based cross sectional study, conducted at Emergency department and Hospital of S.N. Medical  College, Agra. Data were analyzed using SPSS software version 20.0. Results: Out of total 425 RTA cases, majority were males (89.6%).About 7/10th cases (70.1%) occurred during weekdays). Overall, maximum cases (18.1%) occurred on Thursdays. Accord- ing to time distribution trends 69.2% of accidents took place be- tween 12.00 to 7.59 pm. Regarding months and season wise distri- bution, September had the maximum (12.0%) accidents and high- est percentage (40.0%) of accidents occurred in rainy season. This seasonal variation was found to be highly statistically significant (P<0.0001). Conclusion: Although accidents are uniformly distributed throughout the weekdays with slightly higher number of cases be- ing reported on Thursdays and most of the accidents occurred dur- ing rush hours. Significantly higher number of accidents occurred in rainy season.